`y'= d/dx e^(ktan(sqrt(x)))`

`= e^(ktan(sqrt(x))) d/dx (ktan(sqrt(x)))`

`= k e^(ktan (sqrt(x))) * sec^2(sqrt(x)) * d/dx (sqrt(x))`

`= k*e^(ktan(sqrt(x))) * sec^2(sqrt(x))*(1/2 x^(-1/2))`

`= k/(2sqrt(x)) *e^(ktan(sqrt(x))) * sec^2(sqrt(x))`

Hope this helps.

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now